Exploiting the Hydrogen Bond Donor/Acceptor Properties of PN‐Heterocycles: Selective Anion Receptors for Hydrogen Sulfate. (13th March 2019) - Deng, Chun‐Lin; Bard, Jeremy P.; Lohrman, Jessica A.; Barker, Joshua E.; Zakharov, Lev N.; Johnson, Darren W.; Haley, Michael M.
Abstract: We describe two novel hybrid receptors combining a phosphorus‐/nitrogen‐containing (PN) phosphonamidate heterocycle with urea recognition units in an arylethynyl backbone. Structural, spectroscopic and computational studies reveal that the origin of superior binding for hydrogen sulfate (HSO4 − ) anion is correlated with the formation of strong hetero‐complementary hydrogen bonds with the phosphonamidate motif. We further demonstrate that the hybrid host system is capable of capturing/transporting the HSO4 − anion from an aqueous, biphasic system. Abstract : Selektiver Wirt : Die Integration eines starren und cis ‐konfigurierten Phosphonamidats in das Bis‐Arylethinyl‐Monoharnstoffgerüst kann die Selektivität und Affinität für HSO4 − ‐Anionen deutlich erhöhen. Das hybride Wirtsystem kann HSO4 − aus einer wässrigen Quelle unter Bedingungen der flüssig/flüssig‐Extraktion erfassen und transportieren.